Produção da enzima xilose redutase por Candida tropicalis ATCC750 usando hidrolisado hemicelulósico do bagaço de caju - Serpa, Juliana de França (2016)
Xylose reductase enzyme (EC 1.1.1.21) has potential application in the production of xylitol, and is an intracellular enzyme commonly found in yeast. Xylitol is a carbohydrate-alcohol used in food, dental, pharmaceutical and cosmetic industries. The large-scale production of this enzyme, as well as its industrial application for the production of xylitol and other bioproducts, has been limited due to the high price of commercial xylose. This problem has motivated researchers to develop better techniques for reducing the costs of obtaining XR, for example, the search for new raw material and the process conditions. Among possible feedstocks, lignocellulosic materials, as cashew apple bagasse, are low cost sources with potential applications in bioprocesses. In this context, the aim of this study was to evaluate the production of xylose reductase enzyme (XR) and xylitol by biotechnological processes by the yeast Candida tropicalis ATCC750 and hemicellulose hydrolysate from cashew apple bagasse (CAB) as substrate. The hemicellulose hydrolysate from cashew apple bagasse (HBCD) was obtained by acid hydrolysis with diluted sulfuric acid (H2SO4) and it used as a culture medium. The processes were conducted in orbital shaker at 150 rpm and different temperatures (25 °C, 30 °C, 35 °C and 45 °C). The xylose reductase enzyme extracts were used to reduce xylose to xylitol and the XR activity was determined by NADPH oxidation reaction at 25 °C. According to the analyzed data using hemicellulose hydrolysate (HBCD) medium, the highest microbial growth was observed at 25 °C and 30 °C and slightly growth at 40 °C. Under the experimental conditions evaluated, the production of xylitol was not observed, but there were the production of xylose reductase enzyme and ethanol. The XR from Candida tropicalis resulted in a crude extract with a higher enzymatic activity in the temperature of production at 25 °C (0.265 U/mL). In the partial characterization of the enzyme, the optimum pH and temperature were 7.0 and 50 °C, respectively. Subsequently, the gel electrophoresis was performed under denaturing conditions for identification of the enzyme fractions, which identify a heterodimeric structure with a molecular weight of approximately 30 kDa. The results showed that the cashew apple bagasse hydrolysate did not favor the xylitol production in the studied conditions; however, it is a potential means for biotechnological production of the enzyme xylose reductase (XR).